2017
DOI: 10.1155/2017/7053465
|View full text |Cite
|
Sign up to set email alerts
|

Successful Low-Cost Scaffold-Free Cartilage Tissue Engineering Using Human Cartilage Progenitor Cell Spheroids Formed by Micromolded Nonadhesive Hydrogel

Abstract: The scaffold-free tissue engineering using spheroids is pointed out as an approach for optimizing the delivery system of cartilage construct. In this study, we aimed to evaluate the micromolded nonadhesive hydrogel (MicroTissues®) for spheroid compaction (2-day culture) and spontaneous chondrogenesis (21-day culture) using cartilage progenitors cells (CPCs) from human nasal septum without chondrogenic stimulus. CPC spheroids showed diameter stability (486 μm ± 65), high percentage of viable cells (88.1 ± 2.1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
(46 reference statements)
2
31
0
Order By: Relevance
“…The results of our work provide well-established correlation between CS biomechanical properties and the level of ECM accumulation, consistent with studies where TS were fabricated from human cartilage progenitor cells and other cartilage models. 40,41 CS ability to spread on adhesive substrates did not relate to their biomechanical properties. Nevertheless, we observed the well-established connection between CS biomechanical properties and their fusion kinetics, significantly decreasing during maturation process, which seems valuable for prediction of TS behavior after implantation in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…The results of our work provide well-established correlation between CS biomechanical properties and the level of ECM accumulation, consistent with studies where TS were fabricated from human cartilage progenitor cells and other cartilage models. 40,41 CS ability to spread on adhesive substrates did not relate to their biomechanical properties. Nevertheless, we observed the well-established connection between CS biomechanical properties and their fusion kinetics, significantly decreasing during maturation process, which seems valuable for prediction of TS behavior after implantation in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…The differences between our data and those reported in 2D culture studies may result from the tissue-like properties of 3D cultures. The ASC spheroid 3D culture model established in our laboratory (Stuart et al 2017) is expected to have drug diffusion and transport conditions more similar to those observed in tissues in vivo, resulting in more physiological responses to treatment than those obtained with 2D cultures (Edmondson et al 2014). In agreement with this notion, Lee et al (2009) reported that gold nanoparticles were toxic to human hepatocarcinoma (HepG2) in 2D culture, but not to spheroids of these cells, possibly due to the dense cell-cell interaction and extracellular matrix secretion in the spheroids, which leads to changes in the cell phenotype and secretory profile.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of 3D cell culture in toxicity assays may increase the accuracy of in vitro drug testing, by providing assay conditions closer to those found in vivo. Our laboratory has shown that human stem cells derived from adipose tissue (adipose stem cells, or ASCs) form spheroids in vitro under appropriate conditions, and have significant potential in tissue engineering (Stuart et al 2017). Despite the potential of ASC 3D cultures for use in tissue engineering and toxicity analyses, the response of ASCs to AgCl-NPs in spheroid 3D cultures has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our research group has recapitulated in vitro chondrogenic events using spheroids from ASCs (manuscript in preparation) and cartilage progenitor cells. Cartilage progenitor cells spheroids represent an interesting model, since they present gene upregulation of Trio SRY-Box (SOX) up to 200 times compared to monolayer [ 54 ].…”
Section: Developmental Tissue Engineeringmentioning
confidence: 99%